2020
DOI: 10.1590/1678-5150-pvb-5998
|View full text |Cite
|
Sign up to set email alerts
|

Welfare during pre-slaughter handling and carcass lesions of beef cattle submitted to different loading densities

Abstract: Inadequate pre-slaughter handling conditions can compromise animal welfare and productivity. This study aimed to evaluate the animal welfare (AW) indexes during pre-slaughter handling and quantify the carcass lesions of beef cattle submitted to different loading densities. A total of 270 Nellore cattle, at 30 months of age, from three farms were used in the study. Each farm presented a different loading density: higher density (500kg/m2), intermediate density (450kg/m2), and lower density (420kg/m2). Three shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Our results demonstrated an association between bruising and the presence of high-risk conditions of both intrinsic and extrinsic factors and confirm that carcass bruising is a multifactorial issue (85) associated with a complex combination of these factors. (86) For intrinsic risk factors, female cattle, older age groups, the breed, and the amount of fat cover were associated with bruising.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results demonstrated an association between bruising and the presence of high-risk conditions of both intrinsic and extrinsic factors and confirm that carcass bruising is a multifactorial issue (85) associated with a complex combination of these factors. (86) For intrinsic risk factors, female cattle, older age groups, the breed, and the amount of fat cover were associated with bruising.…”
Section: Discussionsupporting
confidence: 82%
“…(87,90) Transportation conditions such as long distances traveled, high load densities, and prolonged times of transportation increased the odds for bruising, though we found no effect for the inclusion of a resting period during the journey or the type of vehicle used. Previous studies have demonstrated an increased chance for bruising when cattle are transported at moderate or high load densities (85) and that exposing cattle to long-distance journeys causes stress, fear, and fatigue that impair animal welfare and increase the frequency of injuries. (91,92) With respect to the handling at the slaughterhouse and the quality of the facilities, we found that cattle exposed to a prolonged unloading time and poor/regular quality of the loading facilities had a higher incidence of bruises.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these animals are more often exposed to multiple stress situations caused by strange environments, animals, and operators [40,41]. It has also been argued that cattle exhibit more aggressive behavior when mixed during pre-mortem operations, which increases the probability of finding carcass bruises, thus affecting the carcass output and compromising meat quality [41,42]. Keeping animals between their familiar partners during finishing, loading, transporting, and slaughtering has been demonstrated as providing a calming effect for the animals, which can result in improved meat quality [38,43].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of bruising across studies is highly variable, ranging from 8.6% to 100% (Table 2). Although there were several studies reporting bruise frequency of less than 25% for at least one population group (Bethancourt-Garcia et al, 2019a, b;Strappini et al, 2010;Brito et al, 2019), the majority of studies reported relatively high bruise prevalence with some reporting over 90% bruising (Jarvis et al, 1995;Jarvis et al, 1996;Huertas et al, 2018;Brennecke et al, 2020;Ferreira et al, 2020) in their study populations. Although not all bruises are the same size or severity, these bruise frequencies are substantial and cause concern both from an economic and welfare standpoint.…”
Section: Carcass Bruisingmentioning
confidence: 93%
“…From the 15 papers that assessed the effect of transport distance or duration on carcass bruising, eight papers reported significant findings (i.e., longer transport increased bruising incidence; Jarvis et al, 1995;McNally and Warriss, 1996;Hoffman et al, 1998;Vimiso and Muchenje, 2013;Silva et al, 2016;Mendonca et al, 2018;Bethancourt-Garcia et al, 2019a;Brito et al, 2019). Similar to evaluating the effects of transport on muscle pH, ample challenges exist for assessing and managing bruising as there are multiple opportunities for bruising to occur along the supply chain (e.g., mixing cattle with different horn statuses, Shaw et al, 1976;Wythes et al, 1979b;high stocking densities, Tarrant et al, 1988;Brennecke et al, 2020;Ferreira et al, 2020;rough pre-slaughter handling conditions, Jarvis et al, 1995;McNally and Warriss, 1996;Mendonca et al, 2018).…”
Section: Carcass Bruisingmentioning
confidence: 99%